KINERJA KEUANGAN KOPERASI SEKOLAH SMA NEGERI 1 TANAH ABANG DALAM HUBUNGANNYA MEMBANGUN SUMBER DAYA MANUSIA BERBASIS SCIENCE DAN TEKNOLOGI - Diana Widhi Rachmawati (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
Cooperative School was established in school enviroment which were the students as member. It can be established in many levels according to the level of education, such as cooperative of elementary school, cooperative of junior high school, cooperative of senior high school, and etc. Analysis of financial report was aplication of tool and technique analysis for financial report of general aims then the data related to generate estimates and the conclusion can be used for business analysis. Analysis of financial report this research used ratio analysis method, that was liquidity ratio, solvency, activity, and profitability. The researcher used quantitative method. This method was the method of research which was gronded on philosophy of positivism, it was used to research specific population and sample. The sampling technique is done randomly, data retrieval used reseach instrument, and data analysis was quantitative statistics to test the hypothesis which had been set. The sample: Cooperative of Senior High School 1 Tanah Abang. The result of reseacrh that cooperative in Senior High School 1 Tanah Abang was liquid. It was caused the cooperative had not made a loan to outsiders and have not implemented the sale and purchase of school supplies but it was only saving and loan cooperative side, it was still pretty sulvable because it only involve the saving and loan, not profit yet because it was still many funds in the members and pretty good activity because the funds rotated from members to members. The researcher hope cooperatives school can envolve their work so it can prosper the members. Keywords— Financial Performance Cooperative School